Effects of water stress on nutrients and enzyme activity in rhizosphere soils of greenhouse grape - Zhang, Rui; Zhang, Hongjuan; Yang, Changyu; Li, Hongxia; Wu, Jiangqi (Frontiers in Microbiology, 2024)
In grape cultivation, incorrect water regulation will lead to significant water wastage, which in turn will change soil structure and disrupt soil nutrient cycling processes. This study aimed to investigate the effects of different water regulation treatments (by setting moderate water stress (W1), mild water stress (W2), and adequate water availability (CK)) on soil physical-chemical properties and enzyme activity in grape during the growing season. The result showed that the W2 treatment had a negative impact on the build-up of dissolved organic carbon (DOC), nitrate nitrogen (NO3-N), and available phosphorus (AP). Throughout the reproductive period, the W1 and W2 treatments decreased the soil’s microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) contents, and MBC was more vulnerable to water stress. During the growth period, the trends of urease, catalase, and sucrase activities in different soil depth were ranked as 10-20 cm>0-10 cm>20-40 cm. The urease activity in 0-10 cm soil was suppressed by both W1 and W2 treatments, while the invertase activity in various soil layers under W1 treatment differed substantially. The W1 treatment also reduced the catalase activity in the 20-40 cm soil layer in the grape growth season. These findings suggested that W2 treatment can conserve water and enhance microbial ecology of greenhouse grape soils. Therefore, W2 treatment was the most effective water regulation measure for local greenhouse grape cultivation.